Comparison of Bite Force with Locking Plates versus Non-Locking Plates in the Treatment of Mandibular Fractures: A Meta-Analysis - Glória, José Cristiano Ramos; Fernandes, Ighor Andrade; Silveira, Esmeralda Maria da; Souza, Glaciele Maria de; Rocha, Ricardo Lopes; Galvão, Endi Lanza; Falci, Saulo Gabriel Moreira (International Archives of Otorhinolaryngology, 2018)
Introduction Mandibular fractures represent a high percentage of all facial fractures, and the bite force is a fundamental parameter to measure the actual mandibular function and, subsequently, the masticatory efficiency and quality of life.Objectives The purpose of the present systematic review was to verify if there is any difference in the bite forces of patients with mandibular fractures fixed by locking or non-locking plates, testing the null hypothesis of no difference in this parameter.Data Synthesis A systematic review of the literature was conducted using four databases (PubMed, Virtual Health Library, Web of Science and Science Direct) without restrictions as to publication date or language. We found 3,039 abstracts, and selected 4 articles for this review.Conclusion The overall results show better performance in bite force for the locking plates when compared with the non-locking plates in the incisor region (mean deviation [MD]: 1.18; 95% confidence interval [95%CI]: 0.13–2.23), right molar region (MD: 4.71; 95%CI: 0.63–8.79) and left molar region (MD: 10.34; 95%CI: 4.55–16.13). Although the results of this study indicated a better bite force result with the locking plates, there is still no sufficient evidence to support this information safely.
Keywords: bite force; mandibular fracture; fracture fixation; bone plates; internal fixators